The Rural Hand Therapy Project - providing hand therapy services closer to home - Sue Williams; Lin Wegener; Gail Kingston (James Cook University, 2023)
Context: Hand therapy optimises functional use of the hand and arm after injury and is an expert area of practice for occupational therapists (OTs) and physiotherapists. In rural Australia, patients frequently travel to metropolitan or larger regional centres for initial hand surgery and rehabilitation. However, rural patients' access to follow-up hand therapy after the initial phase of care is impacted by several factors such as transport options, distance, staff shortages and availability of therapists skilled in hand therapy. To ensure service equity, these challenges require consideration of an alternative model of care that can be provided in rural areas. The aim of this project was to develop a shared care model that would better support rural OTs and rural patients in accessing follow-up hand therapy services closer to home. Issue: Two part-time accredited hand therapists (herein referred to as clinical leads) were employed in 2019-2020 to investigate a suitable model of care. Consultation with key stakeholders identified the following core issues: barriers, enablers, processes and intervention, and technology and resources. These findings were combined with recommendations from the literature to develop a model of service delivery: the Rural Hand Therapy Project (RHTP). Under the RHTP, eligible rural patients with complex hand conditions were either seen for their initial appointment, or had their referral screened, by a clinical lead at the regional hospital (Toowoomba Hospital, Queensland). During this process, a detailed handover to the rural OT was completed. Weekly case conferences with a clinical lead were available to all rural clusters. Rural patient cases remained open at the regional hospital for at least 3 months to allow patients to be easily seen by a clinical lead, face to face, or via telehealth (with the rural OT) if needed. The clinical leads also served as the primary contact for any clinical questions from rural OTs. Additionally, the clinical leads provided support and professional development to rural OTs based on the mix of patient cases at the time. Lessons learned: The RHTP clinical leads were involved in both initial assessment and ongoing intervention for 56% of rural hand therapy patients. The provision of videoconference occasions of service increased from 1% to 8%. Although a low response rate impaired therapist evaluation, an unexpected positive outcome of the RHTP was its flexibility to respond temporarily during rural staff crises and provide vital patient care. The RHTP model of care has shown promise in addressing the challenges faced by rural patients in accessing follow-up hand therapy services closer to home. Further research has been initiated to inform care at a local level. By sharing the model of RHTP, it is hoped that the equity of hand therapy service provision can be increased to improve patient outcomes in other rural and remote localities.